Performance of a solar storage collector - Hazami, M.; Kooli, S.; Lazaar, M.; Farhat, A.; Belghith, A.
The principal application of solar energy in Tunisia is in the production of domestic water heating using thermosyphon systems principally composed of a flat plate solar collector and a storage tank. In order to simplify this system we conceived and realized, in our laboratory, a solar storage collector able to provide hot water which can be exploited for domestic uses. The collector consists of a capillary exchanger integrated in a concrete matrix. To increase the solar radiation effect we covered the collector with a black selective layer. The objective of this work is to study the performance of this system. An experimental study was carried out in order to determine the quantity of water supplied by the storage collector and the thermal energy to be extracted and exploited for agricultural greenhouse heating.
Keywords: SOLAR ENERGY; SOLAR STORAGE COLLECTOR; AGRICULTURAL GREENHOUSE HEATING